SUBALTERNITY IN COSTA RICA: EDUCATIONAL GAPS AND OPPORTUNITIES IN A GLOBALIZED AND DIGITAL SOCIETY - Castellón Zelaya, Luis Arturo (2020)
This article exposes some reflections about the inequalities that affect to take advantage of Costa Rican public education to respond to the current context of globalization and technological development. Based on the theoretical contributions of Gayatri Chakravorty Spivak and Paulo Freire, the transformation of literacy in the context of digital culture is discussed to take advantage of opportunities for a more equitable social development in the country.